THE USE OF INDONESIAN LANGUAGE AS THE FIRST LANGUAGE BY CHILDREN OF THE BALINESE FAMILY (SENTENCE ANALYSIS IN TERMS OF CONTENTS AND STRUCTURE) - Liniati, Ni Wayan; Rasna, I Wayan; Sudiana, I Nyoman (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2019)
This research aimed to describe (1) the use of Indonesian language as the first language in terms of sentence based on the content and structure of children in the Balinese ethnic families and (2) the constraints faced by the Balinese ethnic families in Banjar Bernasi in using the Indonesian language as the first language of their children. The subject of this research was the Balinese family in Banjar Bernasi who used the Indonesian language as the first language of their children. The object of this research was the use of Indonesian language as the first language of children in the Balinese family ethnic in Banjar Bernasi and the constraints faced by the family in Banjar Bernasi in using the Indonesian language as the first language of their children. The data collection methods used were observation method, interview, and recording. There were several steps in analyzing the data, namely data reduction, data presentation, and conclusions. The results showed that (1) the use of Indonesian language as the first language of children in the Balinese ethnic families in Banjar Bernasi in terms of sentence based on the content and structure could be declared that children on the primary school were able to use the sentence well. (2) There was no constraint felt by parents in teaching the Indonesian language to their children. That was because the children had already been using the Indonesian language as a mother language start from the baby. Based on the results of research and discussion, it can be concluded that children were able to use the Indonesian language well in terms of sentences based on the content and structure. Therefore, it is suggested to parents to always teach their children to speak well so that children are able to communicate by using the Indonesian language effectively.